Kumatakenin inhibited iron-ferroptosis in epithelial cells from colitis mice by regulating the Eno3-IRP1-axis - Arenbaoligao,; Guo, Xinrui; Xiong, Jiahao; Zhang, Shuangshuang; Yang, Yuewen; Chen, Dapeng; Xie, Yu (Frontiers in Pharmacology, 2023)
Inhibition of epithelial ferroptosis in colonic tissues relieved clinical symptom and improves endoscopic presentations in inflammatory bowel disease (IBD). Kumatakenin, the main ingredient of traditional Chinese medicines cloves and Alpinia purpurata, is reported to possess numbers of therapeutic benefits. However, whether kumatakenin could inhibited ferroptosis and further alleviate colitis remains unclear. Here we measured the effects of kumatakenin on ferroptosis of colonic epithelial cells from colitis mice. Colitis model was induced in mice by oral intake of 2.5% DSS in the drinking water. RNA_seq assay was performed to measure the mechanism underlying kumatakenin-exerted effects on colitis. Results showed that different doses of kumatakenin significantly alleviated symptom, suppressed intestinal inflammation in colitis mice model. Kumatakenin supplementation decreased cellular iron level and suppressed ferroptosis in epithelial cells from colitis mice. RNA_seq, qPCR and pharmacological inhibition assay showed that kumatakenin reducing cellular iron level and suppressed ferroptosis in epithelial cells from colitis mice at least partially by upregulating enolase (Eno-3) expression. Furtherly, kumatakenin decreased iron level in epithelial cell by modulating Eno3-iron regulatory protein (IRP1) axis. Molecular docking results revealed that kumatakenin could bind to Eno3 through the hydrogen bond interaction with amino acid residues Thr208, Val206 and Pro203. This work will provide scientific basis of kumatakenin in the clinical use for anti-colitis.